ANALISIS PEMAHAMAN KEWIRAUSAHAAN (KEBERHASILAN DIRI,TOLERANSI AKAN RESIKO DAN KEBEBASAN DALAM BEKERJA) TERHADAP MOTIVASI MAHASIWA UNTUK MENJADI ENTREPRENEUR - Abdulah, Abdulah; Andayani, Sri; Pratiwi, Ni Made Ida (Jurnal Dinamika Administrasi Bisnis, 2016)
This study aims to determine the effect of the understanding of entrepreneurship with three factors (personal goals,risk tolerance and freedom will be in the works) to motivate students to become entrepreneurs among student S1 Faculty of Social and Political Science 17 August University of Surabaya. The number of samples in this study were 60 people.. In this study conducted with regression method. Regression models are useful committed against more than one independent variable, to determine its effect on the dependent variable. The result of this study indicate that all variable positive and significant effect on the motivation of students to become entrepreneurs. As for the study of each independent variable, there is also a positive and significant effect on the dependent variable. to determine the effect of the understanding of will be in the works tKata Kunci : Motivasi, keberhasilan diri, toleransi akan resiko, merasakan pekerjaan bebas dan entrepreneu